COLÔNIA BELLA VISTA: UM ESPAÇO CONSTRUÍDO PELAS PRÁTICAS SOCIAIS DOS IMIGRANTES ITALIANOS EM IMBITUVA/PR - Stadler, Cleusi Teresinha Bobato (2015)
The Bella Vista Colony is located in Imbituva / Pr. Its formation took place in 1896, by Italian immigrants who emigrated from the Veneto region, Italy, to the colonies around Curitiba and then to Imbituva. Bella Vista is a colony characterized by Italian descent who built a symbology and an identity through their daily practices. Using the theoretical referential of Pierre Bourdieu (habitus) and Michel de Certeau (practice space), the objective of this dissertation is to understand the formation of Bella Vista colony, in the context of Italian Immigration, highlighting the daily life of the colony, food, farming practices, homes, religion, festivities, weddings and how these aspects bind to the social formation processes and the identities of their descendants in Imbituva. To achieve this objective it was used the oral history as the main methodology, as well as , official documents and photographs analysis to understand the formation of the Colony and TIRAR( through oral story we try to understand) how the Italian cuisines were prepared with emphasis on polenta, how they used to build their houses, how they used to prepare the land and grew grapes for the preparation of wine, which religious festivities they were used to celebrate and how they used to celebrate the marriages between Italian families. With the results, we note that the daily practices in families of descendants contributed and they continue to contribute in the formation of the colony identity, as well they show marks of Italian (Italianity). We highlight that these everyday practices of Italian immigrants were remade, constructing so their descendants identities and traditions that must be related, (identities and therefore the must be reported,) valuing their histories that express through the oral history their values and social experiences in time and space.